Analisis Perilaku ASN Sipir Dalam Melakukan Pembinaan Di Lembaga Pemasyarakatan Kelas II A Pekanbaru - Afrizal Afrizal; Rusdi Rusdi; Afrinaldy Rustam (UIR Press, 2021)
Correctional officers as one of the State Warden Apparatus (ASN) in carrying out their duties are expected to be expected to be professional and in accordance with the provisions of the applicable law. The formulation of the research problem is the behavior of the warden in coaching prisoners, and what are the obstacles in implementing coaching at the Class IIA Pekanbaru Penitentiary?. This type of research is a qualitative research that aims to build a preposition and explain the meaning behind the social reality that occurs. Observation, In-depth Interview and Documentation are the techniques used to collect data. Data were analyzed by data reduction. Data presentation and conclusion. The informants in this study were the Ministry of Law and Human Rights of Riau Province. the Correctional Institution and several inmates. The results of this study are differences in behavior in Correctional Institutions in carrying out basic and different tasks required, different willingness and ability and education possessed. But in general, the warden in carrying out the guidance is in accordance with the goals of the institution, although there are still some shortcomings. There are several advantages in the implementation of coaching, namely excess occupancy capacity, the coaching program cannot run effectively, and the lack of attention from the policy makers in handling the coaching carried out for the inmates.